RAK360-V2: smart solar detector / Khairul Anuar Maarof, Balkhiz Ismail and Mohamad Ezad Hafez Mohd Pahroraji - Maarof, Khairul Anuar; Ismail, Balkhiz; Mohd Pahroraji, Mohamad Ezad Hafez (2020)
Sunlight is an excessive source of energy and this energy can be harnessed successfully using solar photovoltaic (PV) panels and convert it into electrical energy. Therefore, the optimization of the solar system seems to be one of the biggest challenges as the static solar panel has limitations to charge the utmost number of battery life. Thus, the project development is to allow the maximum charging capability of the solar panel. To this end, this project main objective is to present a new approach to maximize solar energy generation and improving efficiency. Hence, to achieve the objectives, this project operated by two (2) solar trackers (Servo-1 and Servo-2) acted as a wheel and being installed to allow 360 degrees movement. The main solar system generates and charging the battery based on the quantity of radiation absorbs by the solar panel. By the flexible movement of the solar panel, the maximum output of the solar radiation can be optimized. Recognizing the gap of prior solar panel, internet of things (IoT) software IoT Solar Apps being installed to monitor the longevity of the battery through mobile phones. Notably, this project can be such as an alternative to reduced cost from electricity consumption and the usage can be induced including commercialization.